The modernization of Japan 1 (Institute of Asian Economic Affairs, 1966)
Contents: The modernization of Japan this volume deals with the initial stage of Japan's modernization. Thirteen leading Japanese and foreign scholars have contributed articles to this volume pursuing the process and the problems of modernization in various fields. It will no doubt be of use to readers in examining modernization, its history and theory, and not only in studies of modern Japan. The comprehensive and synthetic effort will be developed further in the forthcoming volumes of this series